2
$\begingroup$

If $ \sin x + \cos x = a$ , then find:

(i) $ \sin^6 x + \cos^6 x$

(ii) $ \lvert \sin x – \cos x \rvert $

I tried using the identity $a^3 + b^3$ for (i) but that didn't work and I ended up with an expression that was of no help. I have absolutely no idea on how to go about the problem. Any kind of help would be appreciated.

$\endgroup$
3
$\begingroup$

Given $\displaystyle \sin x+\cos x = a\Rightarrow (\sin x+\cos x)^2 = a^2\Rightarrow \sin x \cos x = \frac{a^2-1}{2}$

Using $(\sin ^2 x+\cos^2 x)^3 = (\sin^6 x+\cos^6 x)+3(\sin x\cos x)^2(\sin^2 x+\cos^2 x)$

So $\displaystyle 1=\sin^6 x+\cos^6 x+3\left(\frac{a^2-1}{2}\right)$

$\displaystyle \bullet\; |\sin x-\cos x|^2 = (\sin x-\cos x)^2=1-2\sin x\cos x = 1-\frac{2(a^2-1)}{2}$

$\endgroup$
2
$\begingroup$

We have $$\sin^6 x +\cos^6 x =(\sin^2 x +\cos^2 x)(\sin^4 x + \cos^4 x -\sin^2 x \cos^2 x) $$ $$=(1)((\sin^2 x + \cos^2 x)^2-3\sin^2 x \cos^2 x) $$ $$=(1-3\sin^2 x\cos^2 x) \tag {1}$$

Now we know that $$(\sin x + \cos x)^2 =1 +2\sin x \cos x$$ Use this result to find the value of $(1)$.

For $(2) $, use the fact that $$(\sin x -\cos x)^2 =1-2\sin x\cos x$$ Hope it helps.

$\endgroup$
  • $\begingroup$ I used the same approach for (i) but then couldn't figure out how to use the given information to find it's value. I had absolutely no idea about (ii). Well, thanks a lot. $\endgroup$ – SamInuyasha ANMF Jan 29 '17 at 7:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.